2003
DOI: 10.3319/tao.2003.14.1.63(t)
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Structure, Seismicity, and Fault Structure in the Peikang High Area of Western Taiwan

Abstract: As an attempt to investigate the sub-surface geometry of the Peikang High, and the structural fe atures that may have influenced the regional seismicity of western Taiwan, a three-dimensional (3-D) P-wave velocity model has been developed. The velocity model was determined by simulta neously inverting of P-and S-wave arrival times recorded by the Central Weather Bureau Seismographic Network for earthquakes occurred from 1991 to 2000. In order to have a good constrain for the shallow part of the velocity model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The most important along‐strike change in the south central Taiwan fold‐and‐thrust belt takes place at zone A, which is the on‐land prolongation of the upper part of the necking zone (Figures , and ). Zone A forms the southern flank of Peikang Basement High, which has been widely recognized as an area of significant change in the structure, fault kinematics, and seismicity of the thrust belt [e.g., Lu et al ., ; Deffontaines et al ., ; Lacombe et al ., ; Mouthereau et al ., ; Cheng et al ., ; Mouthereau and Lacombe , ; Wu et al ., , ; Byrne et al ., ; Alvarez‐Marron et al ., ]. It has been suggested that these along‐strike changes are largely due to buttressing [ Hayward and Graham , ] of the thrust system by the basement high [e.g., Lu et al ., ; Lacombe et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…The most important along‐strike change in the south central Taiwan fold‐and‐thrust belt takes place at zone A, which is the on‐land prolongation of the upper part of the necking zone (Figures , and ). Zone A forms the southern flank of Peikang Basement High, which has been widely recognized as an area of significant change in the structure, fault kinematics, and seismicity of the thrust belt [e.g., Lu et al ., ; Deffontaines et al ., ; Lacombe et al ., ; Mouthereau et al ., ; Cheng et al ., ; Mouthereau and Lacombe , ; Wu et al ., , ; Byrne et al ., ; Alvarez‐Marron et al ., ]. It has been suggested that these along‐strike changes are largely due to buttressing [ Hayward and Graham , ] of the thrust system by the basement high [e.g., Lu et al ., ; Lacombe et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Many of the structural and stratigraphic changes that we outline above have been attributed to the Alishan area being located along the southern flank of the Peikang High [e.g., Mouthereau et al , ; Cheng et al , ; Wu et al , ; Byrne et al , ], which comprises a number of approximately east‐northeast trending extensional faults in the footwall to the exposed thrust system. Many of these are buried beneath synorogenic sediments but have been either imaged in reflection seismic data or sampled in boreholes [ Yang et al , ; Chen and Yang , ; Lin et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…The reentrant in the range front observed at the latitude of the Choushui river might be such a feature due to indention by the Peikang High (Figures 2 and 11). This morphological signature is clearly defined, and appears slightly further north than the inferred east‐west present position of this margin horst [e.g., Cheng et al , 2003; Hsu and Sibuet , 1995; Lin et al , 2003] (Figure 2). Transfer faulting, consistent with indentation tectonics, has been described in the area [ Mouthereau et al , 1999].…”
Section: Kinematics Of Deformation Across the Taiwanese Rangementioning
confidence: 94%
“…The Chinese margin shows lateral complexities due to basins and horsts formed during a phase of extension prior to the current collisional regime [e.g., Lin et al , 2003; Teng et al , 1991]. One of these structures, the Peikang High offshore west central Taiwan [e.g., Cheng et al , 2003; Hsu and Sibuet , 1995; Lin et al , 2003], is believed to be responsible for the arcuate geometry of the range front in this region [ Mouthereau et al , 1999] (Figure 2). …”
Section: Structural Framework Stratigraphy and Architecture Of The Fmentioning
confidence: 99%